A method for qualitatively mapping the flood physical vulnerability of residential areas - Doan, To-Uyen Thi; Kanno, Ariyo; Yamamoto, Koichi; Imai, Tsuyoshi; Higuchi, Takaya; Sekine, Masahiko (Vietnam Journal of Science and Technology, 2020)
Mapping flood physical vulnerability is spatially limited because it requires input data such as building structures and materials, which are unavailable on large spatial scales. In this study, we propose a new method for qualitatively evaluating the flood vulnerability of residential areas in the context of the exposure and resilience to flood hazard on large spatial scales. This method utilizes the possible correlations between the structural physical vulnerability and residential types obtained from the statistical classifications of multispectral satellite images. Because multispectral classification is well-established as an inexpensive technique for automatically classifying land cover types over wide areas, our method is feasible and efficient for mapping the physical vulnerability of residential areas. As a case study, we present an application of the proposed approach to the Thach Ha district, Ha Tinh province, Vietnam, using the Japanese type 2 Advanced Visible and Near Infrared Radiometer (AVNIR-2) images and Phased Array type L-band Synthetic Aperture Radar (PALSAR) images captured by the Advanced Earth Observing Satellite (ADEOS).